Integration of Data Mining and Relational Databases - Netz, Amir; Bernhardt, Jeff; Fayyad, Usama; Chaudhuri, Surajit (Proceedings of the 26th International Conference on Very Large Databases, 2000)
In this paper, we review the past work and discuss the future of integration of data mining and relational database systems. We also discuss support for integration in Microsoft SQL Server 2000.